Diversity analysis of sesame germplasm using DIVA-GIS - G Anuradha, S Sivaramakrishnan, Farzana, B Spandana, N Sivaraj, G John Prasanna R (Journal of Spices and Aromatic Crops, 2012)
Sesame (Sesamum indicum L.) was studied for its distribution and diversity in India using DIVAGIS. Grid maps were generated for diversity analysis of the eight quantitative traits viz., plant height, inter-node length, leaves per plant, number of flowers per plant, number of capsules per plant, number of seeds per capsule, seed weight and seed yield. The results indicated that diverse accessions for all these traits can be sourced from Maharashtra, Gujarat and Madhya Pradesh (partly covering Chattisgarh) states and these states are diversity rich pockets for sesame germplasm in India.